Changes of the groundwater quality threat of main useful aquifer by nitrates from agricultural sources - Zabłocki, Sebastian (Bulletin of Geography. Physical Geography Series, 2015)
The article presents the results of research, conducted in the central Poland, where agriculture is dominant type of land use. This activity is considered as a common potential threat to groundwater quality by nitrates, especially for small groundwater intakes used for the purpose of rural water supply. For this kind of intake seven scenarios of groundwater quality threat were done based on the results of the hydrodynamic modelling researches in this area contained: calculation of volume and time of leakage through the aquitard formations to main useful aquifer, verification of the indirect protection zone and defining the size of the area from which groundwater flows into the intake. The scenarios considered the current groundwater quality threat as well as changes in agricultural land use or changes in fertilizer doses needed to decrease groundwater threat by nitrates in the intake.